1981
DOI: 10.1007/bf00278855
|View full text |Cite
|
Sign up to set email alerts
|

Human transferrin (Tf) and group-specific component (Gc) subtypes in Tunisia

Abstract: Simultaneous subtyping of two genetic markers--group-specific component (Gc) and transferrin (Tf)--by electrofocusing enabled us to compute the following gene frequencies for the Tunisian population: Gc1S, 0.525; Gc1F, 0.260; Gc2, 0.215; TfC1, 0.770; TfC2, 0.215; TfD1, 0.015. The frequencies of TfD, TfC2, and Gc1 are higher than those found in Caucasoid populations and can be explained by Negroid contribution. A selective advantage related to the metabolic role of this vitamin D-binding protein does not seem v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Populations from the Middle East, such as the Bedouins from North Yemen and the Kurds from Iraq, are characterized by lower Gc2 and markedly higher GclF allele frequencies than are found in Europeans. They constitute a different cluster in which the Druses from Israel (Cleve et al, 1978) and the Berbers from Tunisia (Lefranc et al, 1981) could be included. In contrast with other North Africans, the Berbers are genetically related to Middle Eastern Groups.…”
mentioning
confidence: 99%
“…Populations from the Middle East, such as the Bedouins from North Yemen and the Kurds from Iraq, are characterized by lower Gc2 and markedly higher GclF allele frequencies than are found in Europeans. They constitute a different cluster in which the Druses from Israel (Cleve et al, 1978) and the Berbers from Tunisia (Lefranc et al, 1981) could be included. In contrast with other North Africans, the Berbers are genetically related to Middle Eastern Groups.…”
mentioning
confidence: 99%
“…However, the latter allele has not been clearly distinguished from T f :4. The Tf subtypes have been studied in several Eu ropean and Asian populations [1,6,9,12,14,17]. So far, no TfC subtypes have been reported from the Pacific and Australian area, with the exception of Beckman et al [1] who subtyped a small series of 18 Po lynesians living in Hawaii.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a genotyping study of a healthy Korean population reported that GC1F (c.1296T; c.1307C) was predominantly present (49%) followed by GC2 (c.1296T; c.1307A) (33%) (Kim et al, 2019 ). Though GC1F (c.1296T; c.1307C) was found to be predominant in Africans, some exceptions were reported in North‐East African populations, where frequencies of GC1S (c.1296G; c.1307C) (>0.50) were higher than frequencies of the GC1F (c.1296T; c.1307C) subtype (<0.50) (Constans et al, 1980 ; Langer‐Gould et al, 2018 ; Lefranc et al, 1981 ; Navas‐Nazario et al, 2014 ). Furthermore, the frequency of GC2 (c.1296T; c.1307A) was reported to be sporadic in Africa from a complete absence in the Tuareg Kel Kummer population in Mali (Constans et al, 1980 ) to a frequency of 0.21 within the Tunisian population (Lefranc et al, 1981 ).…”
Section: Introductionmentioning
confidence: 99%